Description of two new species of the genus Tmesiphodimerus gen. n. (Coleoptera: Staphylinidae: Pselaphinae) from South Asia - Yin, Zi-Wei; Coulon, Georges; Li, Li-Zhen (Zootaxa, 2013)
Tmesiphodimerus Coulon and Yin, new genus (Pselaphitae: Tmesiphorini) is proposed for T. sinensis Yin and Coulon, new species from Hainan, South China (type species), and T. malaysianus Coulon and Yin, new species from Perak, West Malaysia. The new taxa are described, with their major diagnostic features illustrated. The taxonomic placement of Tmesiphodimerus is discussed.